Care pathways in invasive meningococcal disease: a retrospective analysis of the French national public health insurance database - Catherine Weil-Olivier; Muhamed-Kheir Taha; Stéphane Bouée; Corinne Emery; Véronique Loncle-Provot; Gaëlle Nachbaur; Ekkehard Beck; Céline Pribil (Taylor & Francis Group, 2022)
Invasive meningococcal disease (IMD) carries a high burden in terms of mortality, long-term complications, and cost, which can be significantly reduced by vaccination. The objectives of this case-control study were to document the care pathways of patients with IMD before, during, and after hospitalization and to assess in-hospital complications and long-term sequelae. Cases consisted of all people hospitalized for IMD in France between 2012 and 2017. Controls were matched by age, gender, and district of residence. Data were extracted from the French national public health insurance database on demographics, hospitalizations, mortality and potential sequelae of IMD. Overall, 3,532 cases and 10,590 controls were assessed and followed up for 2.8 years (median). During hospitalization, 1,577 cases (44.6%) stayed in an intensive care unit, 1,238 (35.1%) required mechanical ventilation, and 43 (1.2%) underwent amputation; 293 cases (8.3%) died in hospital and a further 163 (4.6%) died following discharge; 823 cases (25.4% of survivors) presented ≥1 sequela and 298 (9.2%) presented multiple sequelae. The most frequently documented sequelae were epilepsy (N = 205; 5.8%), anxiety (N = 196; 5.5%), and severe neurological disorders (N = 193; 5.5%). All individual sequelae were significantly more frequent (p < .0001) in cases than controls. Hearing/visual impairment and communication problems were conditions that presented the highest risk for cases compared to controls (risk ratios >20 in all cases). In conclusion, this study highlights the importance of providing optimal medical care for patients with IMD, of minimizing the delay before hospitalization, and of effective prevention through comprehensive vaccination programs.